Buhârî'nin Kitâbü't-Tefsîr'inde Dil Bilimsel Yorumlar - Erdoğan, Muhammet (İstanbul Sabahattin Zaim Üniversitesi, 2025)
Bu çalışmada İmam Buhârî’nin el-Câmiu’s-Sahîh isimli eserinin bölümleri içerisinde bulunan eserinde yer alan Kitâbu’t-Tefsîr’deki Lügavî yorumları incelenmiş ve bu yorumlara yapılan bazı eleştiriler ele alınmıştır. Giriş kısmında araştırmanın konusu, önemi, amacı, metodu ve kaynakları hakkında bilgi verilmiştir. Birinci bölümde ilk olarak İmâm Buhârî’nin kısaca hayatı, yaşadığı dönem, ilmî yolculukları, eserleri, hocaları ve talebeleri serdedilmiştir. Ayrıca Buhârî’nin Arap dili ile olan ilişkisi ve onun bu konudaki yetkinliği ortaya konulmaya çalışılmıştır. Bununla daha sonra ele alacağımız lügavî yorumların daha net anlaşılması amaçlanmıştır. İkinci bölümde Buhârî’nin lügavî yorumları incelenmiştir. Bu bölüme, Sahîh-i Buhârî’nin tanıtımı ile başlanmış, Kitabu’t-Tefsîr’in genel özelliklerinden bahsedilmiştir. Ayrıca Buhârî’nin filolojik kaynakları üzerinde durulmuştur. Garîbu’l-Kur’ân kavramı inceledikten sonra Buhârî’nin Lügavî yorumları tahlil edilmeye çalışılmıştır. Ayrıca yorumlanan kelimelerin meallere yansımalarına da değinilmiştir. Bu şekilde Buhârî’nin filolojik tahlillerinin özellikleri tespit edilmeye gayret edilmiştir. Üçüncü bölümde hem geçmiş hem günümüz ilim adamları tarafından Buhârî’nin filolojik yorumlarına getirilen bazı tenkitleri arz edilmiş bunların ayetlerin anlaşılmasında etkisi ortaya koyma hedeflenmiştir. Çalışmamızda Buhârî üzerine yazılan şerhler, bazı önemli sözlükler, tefsirler incelenmiş hem güncel hem de eski eserler taranmıştır.

In this study, the Lügavî interpretations in Kitâbu't-Tafsîr, which is included in the chapters of Imam Bukhari's work named al-Câmiu's-Sahîh, were examined and some criticisms made to these interpretations were discussed. In the introduction part, information is given about the subject, importance, purpose, method and sources of the research. In the first part, firstly, the life of Imam Bukhari, the period he lived, his scientific journeys, works, teachers and students are revealed. In addition, Bukhari's relationship with the Arabic language and his competence in this subject have been tried to be revealed. With this, it is aimed to understand the lexical interpretations that we will discuss later. In the second part, Bukhari's lexical interpretations are examined. This chapter started with the introduction of Sahih-i Bukhari, and the general features of Kitabu't-Tafsîr were mentioned. In addition, Bukhari's philological sources are emphasized. After examining the concept of Garîbu'l-Qur'an, Bukhari's Lügavî interpretations were tried to be analyzed. In addition, the reflections of the interpreted words on the translations are also mentioned. In this way, the characteristics of Bukhari's philological analyzes were tried to be determined. In the third chapter, some criticisms of Bukhari's philological interpretations by both past and present scholars have been presented, and it is aimed to reveal the effect of these on the understanding of the verses. In our study, commentaries, some important dictionaries and commentaries on Bukhari were examined and both current and old works were scanned.
Linguistic Interpretations in al-Bukhari's Kitab al-Tafsir
Keywords: Buhâri; Sahih; Kitabü’t-Tefsir; Lügavi; Yorum; Bukhari; Dictionary Comments; Linguistic; Description